Antioxidant status and lipid peroxidation in the blood of breast cancer patients of different ages - Kasapović, Jelena; Pejić, Snežana; Todorović, Ana; Stojiljković, Vesna; Pajović, Snežana B. (Cell biochemistry and function, 2008)
Oxidative stress is considered to be implicated in the pathophysiology of breast cancers. In this study we investigated the level of oxidative stress and antioxidant (AO) status in the blood of breast cancer patients of different ages. The level of lipid hydroperoxides (LP) was measured in blood plasma and the activities of copper, zinc superoxide dismutase (CuZnSOD), catalase (CAT), glutathione peroxidase (GPx), and glutathione reductase (GR) enzymes, as well as the level of total glutathione (GSH) and CuZnSOD protein were measured in blood cells of breast cancer patients and age‐matched healthy subjects. Our results showed that breast carcinoma is related to increase of lipid peroxidation in plasma with concomitant decrease of AO defense capacity in blood cells, which becomes more pronounced during aging of the patients. Suppression of CuZnSOD activity related to breast cancer is most likely caused by decreased de novo synthesis of this enzyme. Similar patterns of suppression in CuZnSOD and CAT activities related to aging were recorded both in controls and patients. Age‐related decrease in CuZnSOD activity seems not to be caused by altered protein levels of this enzyme. Suppression of AO enzymes associated with breast cancer and aging is most likely the cause of increased levels of reactive oxygen species (ROS). Our results indicate significant role of oxidative‐induced injury in the breast carcinogenesis, particularly during the later stages of aging. Overall, our data support the importance of endogenous AOs in the etiology of breast cancer across all levels of predicted risk. Copyright © 2008 John Wiley & Sons, Ltd.